2021
DOI: 10.21037/tp-20-370
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study on the tip localization of peripherally inserted central catheter (PICC) guided by intracavitary electrocardiography in newborns: a randomised trial

Abstract: Background: The present study aimed to investigate the P-wave changes in intracavitary electrocardiography (IC-ECG) during catheterization with a peripherally inserted central catheter (PICC) in order to provide guidance for the accurate localization of the tip of the PICC.Methods: A total of 106 newborns who needed a PICC were randomly divided into two groups-a study group and a control group-using a random number table, with 53 cases in each group. In the study group, the ECG monitor was connected after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…Foram 20 (62,5%) os artigos incluídos que abordaram o posicionamento do PICC no recém-nascido; onze (34,4%) apresentaram estratégias de posicionamento ideal do cateter por meio de USG e ecocardiografia, [26][27][34][35][36][37][38][39][40][41][42] um (3,1%) o USG em associação com infusão de solução salina agitada, 43 seis (18,8%) a eletrocardiografia intracavitária, 24,[44][45][46][47][48] e dois (6,3%) a radiografia. 16,49 Dos cateteres considerados bem-posicionados por meio de radiografia, 25% estavam em posição intracardíaca na avaliação por USG.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Foram 20 (62,5%) os artigos incluídos que abordaram o posicionamento do PICC no recém-nascido; onze (34,4%) apresentaram estratégias de posicionamento ideal do cateter por meio de USG e ecocardiografia, [26][27][34][35][36][37][38][39][40][41][42] um (3,1%) o USG em associação com infusão de solução salina agitada, 43 seis (18,8%) a eletrocardiografia intracavitária, 24,[44][45][46][47][48] e dois (6,3%) a radiografia. 16,49 Dos cateteres considerados bem-posicionados por meio de radiografia, 25% estavam em posição intracardíaca na avaliação por USG.…”
Section: Resultsunclassified
“…24,[44][45][46][47][48] A ecocardiografia intracavitária verifica o posicionamento do PICC na veia cava por meio de alterações na onda P quando a ponta do cateter atinge a veia cava na junção atrial. [60][61] Os artigos demonstraram sucesso no uso do ECG para o posicionamento adequado do PICC, 24,[44][45][46][47][48] sendo considerado um método acessível e confiável, mais econômico 45,[47][48] e mais rápido comparado às radiografias, 45,48 que reduz a exposição à radiação, 45,47 e a ocorrência complicações associadas. [45][46] É um procedimento simples, mas que demanda habilidade do profissional.…”
Section: Resultsunclassified
“…In recent years, IC-ECG has been widely used for locating the ECC tip, especially in neonates. Growing evidence suggests that IC-ECG is a safe, accurate, easy, and immediate approach for intraoperative ECC tip confirmation [ 6 , 8 , 10 , 11 , 14 , 16 18 , 20 ]. To our knowledge, this retrospective analysis is the first study to quantitatively describe the major changes in IC-ECG for ECC via the lower extremity and determine its effectiveness and safety, which extends upon previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ECC reference length was based on anatomical markers, while the actual insertion length was determined by IC-ECG, and the difference between the two was statistically significant ( P < 0.001). In neonates, increasing evidence has shown that IC-ECG-guided ECC placement can achieve more accurate tip positioning in the first attempt and reduce catheter-related complications [ 6 , 8 , 10 , 14 , 16 , 17 , 20 , 32 ]. Thus, it is necessary and valuable to use IC-ECG to locate the catheter tip during ECC catheterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation